Difficult-to-treat psoriatic arthritis: refining the definition using a statistical model in a real-life cohort - Favalli, Ennio Giulio; Biganzoli, Giacomo; Cincinelli, Gilberto; Ferrito, Matteo; Luconi, Ester; Manara, Maria; Biggioggero, Martina; Boracchi, Patrizia; Caporali, Roberto (Frontiers in Medicine, 2024)
The study aims to test the D2T PsA definition translated from rheumatoid arthritis within a singlecenter observational cohort of PsA patients treated with b/tsDMARDs. In addition, we aimed to identify a numerical index defining D2T-PsA based on a ratio between observed and expected failed b/tsDMARDs, and to exploit a predictive model to identify features associated with the D2T condition.The study enrolled 267 consecutive adult PsA patients receiving b/tsDMARDs and collected demographic, clinical, and clinimetric data. The prevalence of D2T PsA patients was first determined using a proposed definition., and We then developed aa predictive model to assessed the difficulty of treatment of PsA patients based on failed b/tsDMARDs normalized by expected failures. A generalized linear model explored clinical and demographical features associated with difficult-to-treat patients, with a bagging procedure for robust variable selection to include in a univariate analysis and a multivariable model.Of the 267 patients, only 8 (2.9%) met the D2T PsA criteria. Applying the predictive model to 177 patients, 17.2% exhibited higher difficultness-to-treat. Univariate analysis identified associations between difficultness-to-treat and female sex, psoriasis pattern, fibromyalgia presence, and steroid therapy. Multivariate analysis confirmed associations with fibromyalgia, nail and pustular psoriasis, and steroid use.The proposed D2T PsA definition captured only a small proportion of patients with increased treatment difficulty according to the predictive model. These findings suggest potential criteria refinement for defining D2T PsA patients, providing insights for better managing treatment complexities in PsA.